2019
DOI: 10.1109/access.2019.2930133
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Steganographic Code and its Application in Voice-Over-IP Steganography

Abstract: Voice-over IP (VoIP) technology is a kind of digital transmission technology based on IP network. It is one of the important methods to use voice service in VoIP as steganographic carrier to ensure secure transmission. However, the traditional steganographic code has some problems, such as low embedding efficiency and weak concealment, which cannot meet the requirements of VoIP streaming media information hiding for the security of secret information. Therefore, a steganographic algorithm combining F5 and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Xin et al proposed an adaptive audio steganographic algorithm for covert wireless communication, which was based on variable low bit coding [22]. Zhang et al [23] suggested a F5 and simplified wet paper code (SWPC) based algorithm for VoIP steganography, but the tradeoff between the embedding rate and the embedding efficiency was not discussed. Overall, previous steganography studies mainly focused on steganographic algorithm design.…”
Section: Related Workmentioning
confidence: 99%
“…Xin et al proposed an adaptive audio steganographic algorithm for covert wireless communication, which was based on variable low bit coding [22]. Zhang et al [23] suggested a F5 and simplified wet paper code (SWPC) based algorithm for VoIP steganography, but the tradeoff between the embedding rate and the embedding efficiency was not discussed. Overall, previous steganography studies mainly focused on steganographic algorithm design.…”
Section: Related Workmentioning
confidence: 99%
“…Science and technology with information technology as the core have been widely used in important national infrastructure fields such as finance, communications, energy, transportation, education, scientific research, social security and social security [10,11]. As an important information infrastructure, the information and communication industry is one of the main components of the information industry and the pillar of the information industry [12,13]. Under the macro background of China's reform, opening up and economic construction, which has achieved a series of remarkable results, in order to better develop the national economy, promote social progress, adapt to the global development trend of informatization, and strive to improve the country's comprehensive competitive strength, the Chinese government actively draws on the development experience of developed countries and regions in the world, judges the hour and sizes up the situation, seizes development opportunities, and clearly puts forward the development strategy of "promoting industrialization with informatization" in the "Tenth Five-Year" Plan for National Economic and Social Development, and the communication industry is implemented as China.…”
Section: Introductionmentioning
confidence: 99%
“…The Asterisk PBX software should also be used to expand the range of additional features such as call routing, voice mail, conference calls and call recording [9,10]. To ensure the security of the network built on the basis of Asterisk PBX, there is a wide range of security features, such as encryption, authentication, and authorization, which help protect against unauthorized access to the system and data [11][12][13]. For such setups, the Asterisk PBX software is highly available, which means that it can automatically fail over to a standby server in the event of a hardware failure or other problem, ensuring that services are always available [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%